Microwave Radiation Caused Dynamic Metabolic Fluctuations in the Mammalian Hippocampus - Yu Xin; Shu-Ting Guan; Ke Ren; Hui Wang; Ji Dong; Hao-Yu Wang; Jing Zhang; Xin-Ping Xu; Bin-Wei Yao; Li Zhao; Chang-Xiu Shi; Rui-Yun Peng (Metabolites, 2024)
To investigate the dynamic changes in hippocampal metabolism after microwave radiation using liquid chromatography in tandem with mass spectrometry/mass spectrometry (LC–MS/MS) and to identify potential biomarkers. Wistar rats were randomly assigned to a sham group and a microwave radiation group. The rats in the microwave radiation group were exposed to 2.856 GHz for 15 min for three times, with 5 min intervals. The rats in the sham group were not exposed. Transmission electron microscope revealed blurring of the synaptic cleft and postsynaptic dense thickening in hippocampal neurons after microwave radiation. Metabolomic analysis revealed 38, 24, and 39 differentially abundant metabolites at 3, 7, and 14 days after radiation, respectively, and the abundance of 9 metabolites, such as argininosuccinic acid, was continuously decreased. After microwave radiation, the abundance of metabolites such as argininosuccinic acid was successively decreased, indicating that these metabolites could be potential biomarkers for hippocampal tissue injury.